Influence of cryotherapy on balance and joint position sense in healthy subjects: randomized clinical trial. - Lins, Caio Alano de Almeida; Macedo, Liane de Brito; Silveira, Renata Augusta Gomes; Borges, Daniel Tezoni; Brasileiro, Jamilson Simões (Manual Therapy, Posturology & Rehabilitation Journal, 2015)
Background: Cryotherapy has been widely used in clinical practice, particularly for the treatment of acute injuries to soft tissues and various joints. However, since decrease in temperature can results in reduced nerve conduction velocity and proprioception, it can therefore be assumed that cryotherapy, applied before exercise, can result in a greater predisposition of the joints to lesion. Thus, the objective of this study was to evaluate the influence of cryotherapy on balance and knee joint position sense (JPS). Methods: We conducted a randomized single-blinded clinical trial, with thirty volunteers of both genders (age: 23.3 ± 2.5 years; BMI: 22.2 ± 2.1 Kg/m2 ), who were randomly distributed into two groups with 15 subjects in each: control group - 20 minutes at rest; and experimental group - application of cryotherapy on the knee of the dominant lower limb, for 20 minutes. All subjects were submitted to the assessment of the balance, by means of computerized baropodometry and the JPS of the knee of the dominant lower limb (DLL) using an electrogoniometer, both open kinetic chain (OKC) and closed kinetic chain (CKC), before and after the interventions. Statistical analysis was performed using SPSS 20.0 software. Kolmogorov-Smirnov test was used to check the data normality and two-way ANOVA to verify intra and inter-group differences. The study was approved by the local Research and Ethics Committee (Approval no. 099/10). Results: There was a difference on the JPS assessed in OKC in the experimental group (p= 0.03). There was no alteration in the balance and the JPS with CKC, in none of the groups tested (p > 0.05). Conclusion: Cryotherapy when applied on knee did not affect balance or the JPS with CKC of the knee, although alteration was observed in OKC. We therefore conclude that application of cryotherapy before exercises do not posses increased risk of myoarticular injuries, since the most of these activities is performed in CKC.